Two Layer Security Combining MSB Based Steganography and RSTEG With Cryptography - P I, Sumayya; K, Sheena Kurian (IJRDO -Journal of Computer Science Engineering, 2015)
The sharing of sensitive information along a common communication channel has become inexorable in this internet era. Variant techniques are available to ensure the security of private data according to the specific needs. A new way of securing the data is proposed here which makes use of the combination of two data securing techniques. AES cryptography is utilized in combination with a new steganographic technique. The technique improves the security, as the message is not directly embedded in the cover image, instead a status check is done. Accordingly an indication is provided whether at a calculated bit position of the pixel, the actual message bit or its toggled form is present. The position to be compared with message bit is based on the users choice, which specifies which all color components of the pixel to be used. The proposed method uses the MSB bits of pixels for decision making. Multilevel steganography is done by incorporating retransmission steganography. It is effortful for a snooper to retrieve the actual message as it is very different from the common LSB method. The Mean Square Error (MSE) and Peak Signal-to-Noise Ratio (PSNR) and the histogram differences can be used to measure the image quality and efficiency of the technique